Oncogenic K-ras Induces Mitochondrial OPA3 Expression to Promote Energy Metabolism in Pancreatic Cancer Cells - Ning Meng (Cancers, 2019)
K-ras (Kirsten ras GTPase) mutations are oncogenic events frequently observed in many cancer types especially in pancreatic cancer. Although mitochondrial dysfunction has been associated with K-ras mutation, the molecular mechanisms by which K-ras impacts mitochondria and maintains metabolic homeostasis are not fully understood. In this study, we used two K-ras inducible cell systems, human pancreatic epithelial/ K-rasG12D (HPNE/K-rasG12D) and human embryonic kidney cells with tetracycline repressorT-Rex/K-rasG12V, to evaluate the role of oncogenic K-ras in regulating mitochondrial function. Among a panel of genes known to affect mitochondria, only the expression of OPA3 (optic atrophy protein 3) was consistently up-regulated by K-ras activation in both cell lines. Importantly, high expression of OPA3 was also observed in clinical pancreatic cancer tissues. Genetic knockdown of OPA3 caused a significant decrease of energy metabolism, manifested by a suppression of oxygen consumption rate (OCR) and a decrease in cellular ATP content, leading to inhibition of cell proliferation capacity and reduced expression of epithelial−mesenchymal transition (EMT) markers. Our study suggests that OPA3 may promote cellular energy metabolism and its up-regulation in K-ras-driven cancer is likely a mechanism to offset the negative impact of K-ras on mitochondria to maintain energy homeostasis. As such, OPA3 could be a potential target to kill cancer cells with K-ras mutations.